STRATEGI KEPALA SEKOLAH DALAM MEMBENTUK KARAKTER SISWA MELALUI NILAI-NILAI KE-NU-AN DI MA NU SIDOARJO - Noviatul Laili Fitriah; M. Athoiful Fanan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to examine the principal's strategy in shaping students' character based on NU values at MA NU Sidoarjo. This study uses a qualitative case study approach, where data is collected through interviews, observations, and documents. After the data is collected, it is analyzed through data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the strategies implemented by the principal can be analyzed using Henry Mintzberg's 5P theory (Plan, Pattern, Position, Perspective, and Ploy). The approach is as follows: 1) Plan: the principal designs character programs based on NU values, such as tahlilan, istighotsah, and strengthening Aswaja. 2) Pattern: there is consistency in the implementation of routine religious activities that shape students' religious behavior patterns. 3) Position: The school positions itself as an educational institution based on Ahlussunnah wal Jama'ah an-Nahdliyah. 4) Perspective: NU values become a perspective that is internalized in the school culture and daily educational practices. 5) Ploy: Strategies are used to overcome the challenges of instilling religious values in the digital age. With these strategies in place, the principal plays a significant role in shaping the students' character holistically based on Islamic values that are rahmatan lil'alamin.